A lightweight single-phase AlTiVCr compositionally complex alloy. (15th January 2017) - Qiu, Y.; Hu, Y.J.; Taylor, A.; Styles, M.J.; Marceau, R.K.W.; Ceguerra, A.V.; Gibson, M.A.; Liu, Z.K.; Fraser, H.L.; Birbilis, N.
Abstract: A lightweight (5.06 g cm −3 ) AlTiVCr compositionally complex alloy consisting of four elements is presented. Interest in the system is due to its microstructural uniformity and the use of commodity elements. The focus of the present work was to highlight the systematic microstructural and chemical characterization – and the information gained by application of various physical and modeling techniques in concert – in the context of complete characterization of compositionally complex alloys. Herein, analysis of as-cast AlTiVCr was investigated via conventional and scanning transmission electron microscopy, revealing a simple, single-phase microstructure. Characterization was supported by atom probe tomography and X-ray diffraction, whilst first-principles calculations based on density functional theory (DFT) were employed to calculate the thermodynamic and structural properties of the AlTiVCr alloy. The study was able to reveal the unique atomic locations in the alloy, whilst revealing that the B2 phase has a lower formation enthalpy (−9.30 kJ/mol atom) and is more stable than the disordered BCC phase (−1.25 kJ/mol atom) at low temperatures. The study herein provides insight into the combined analysis methods as relevant to the study of compositionally complex and high entropy alloys, indicating means of unambiguous characterization employing generalized multicomponent short range order analysis. Graphical abstract: Image 1